Randomness analysis of pseudo random noise generator using 24-bits LFSR - Yaacob, Siti Hazwani; Khan, Sheroz; Al-Khateeb, Khalid A. Saeed; Siddiqi, Mohammad Umar; Habaebi, Mohamed Hadi; Shahid, Zeeshan (The Institute of Electrical and Electronics Engineers, Inc., 2014)
We have described in previous work the generation of PN-sequence by employing a 4-bit shifted Linear Feedback Shift Register (LFSR) for application into Direct Sequence Spread Spectrum (DSSS) system by simulation. In this paper, is proposed a pseudo random number generator (PRNG) circuit consisting of 24-bit shift registers (LFSR) which has much longer period to improve statistical properties. We simulated the LFSR circuit by using Multisim 11.0 and the pseudo random sequence generated is tested with statistical test of NIST Test suite. The sequence is passed the entire selected test and we concluded that our pseudo random sequence has long enough period to be considered as random.